Implementing change at the Sunnyhill Health & Racquet Club - Chard, Chris; McCrory, Liam; Spence, Kirsty; Milligan, Matthew (London : Human Kinetics, Inc, 2022)
In this case, challenges related to enacting change within a small, private, not-for-proﬁt tennis club in a wealthy suburban community are considered. David Wilson, President of the Sunnyhill Health & Racquet Club, is tasked with developing a plan to address areas of concern within the club's physical infrastructure toward possible upgrading of the club. With a diverse range of members (and their associated interests) and community stakeholders gathering to inﬂuence the decision, the case presented allows for rich discussion on change management strategies. Indeed, as Wilson is met with severe resistance to a unilaterally designed grandiose design by these constituents, it is subsequently left to him and a third-party team of analysts to present a spectrum of plans to both address the issues at the club and meet members' various needs and wants.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Organizational behavior -- Case studies; Management -- Case studies; Tennis clubs -- Case studies